Respiratory syncytial virus infection and bronchial hyperreactivity in children up to two years of age in correlation with atopy - Relić, Tijana; Ilić, Nevenka; Kostić, Gordana; Jovanović, Dara; Tambur, Zoran; Lazarević, Ivana (Vojnosanitetski pregled, 2017)
Background/Aim. Bronchiolitis in early childhood caused by respiratory syncytial virus (RSV) is considered to be important risk factor of the recurrent wheezing and asthma development. The aim of this study was to examine the frequency of RSV infection and atopy in children up to two years of age and to determine their correlation with bronchial hyperreactivity. Methods. The study included 175 children aged 5–24 months. The presence of RSV infection was identified by serum levels of IgA and IgG determined by ELISA. Bronchial hyperreactivity (BHR) has been defined as the existence of chronic bronchial disease and/or three or more previous suspected diagnosis of acute bronchial disease. Atopy was confirmed by detection of the specific serum IgE using quantitative multitest Phadiatop infant (cut off ≥ 0.35 kUA/L). Results. The children with atopy were more frequently infected with RSV (43.3%) than those without atopy (22.8%; p = 0.02). The higher frequency of RSV infection was found in children with BHR in comparison with those without it but only in the group who also had atopy (77.8% vs 28.6%, p = 0.018). In the female children, BHR and RSV infection were associated in 62.5% of cases, regardless the atopy. In the male children with atopy, RSV infection was associated with BHR in 83.3% of the cases, while in those without atopy, RSV infection with BHR was found in only 17.4% of the cases. Conclusion. Children up to two years of age with atopy are more frequently infected with RSV (43.3%) than non-atopic children. Every third child with atopy develops BHR and 77.8% of them also have RSV infection. Atopic children are at higher risk for development of BHR when infected with RSV also.
Keywords: respiratory syncytial viruses; bronchial diseases; hypersensitivity; immediate; comorbidity; child; serbia